"Мала війна" на Волині в 1812 році - Хоміч, Дмитро; Khomich, Dmytro (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто військово-стратегічну ситуацію на території Волинської губернії наприкінці серпня – на початку вересня 1812 року. Показано хід та специфіку бойових дій між російськими та австро-польсько-саксонськими військами у зазначених територіальних і хронологічних межах.

Today, in spite of recent celebration of 200-years-old anniversary of victory of the Russian empire in opposition with Napoleon’s France, contemporaries rarely reminisce that Volyn was the unique Ukrainian territory which the active battle actions of the outlined period were conducted within the limits of. This article examines the military-strategic situation in Volhynia in late August − early September 1812. Specified on the root causes and peculiarities of hostilities in between the Austro-Polish-Saxon and Russian forces in the so-called «Little War», the basic military clashes between the warring parties in these regional and chronological framework. First systematized and analysed historiography of problem during research used considerable array of historical information about marked problem.
«Little War» in Volyn in 1812
Keywords: Волинь; "мала війна"; "болотне сидіння"; р. Стир; австрійці; саксонці; поляки; росіяни; Volyn; «Little War»; «marsh seat»; Styr river; Austrians; Saxons; Poles; Russians